(untitled) (Atlas Journal of Biology, 2020)
Understanding the impact of radiation on occupational workers has been a huge concern; particularly when it comes to cancer, which is considered as a stochastic effect from radiation. This paper aims at investigating the effect of low radiation dose on tumor markers tests among Radiation Workers (RWs). Additionally, it aims at demonstrating the effect of independent variables, such exposed dose, smoking status, and the type of work on tumor markers. As for the methodology, the researchers have retrospectively reviewed collected database of tumor marker tests in four Governmental Hospitals between the period (2013- 2019) to trace the patterns of tumor marker over the years. The exposed dose record was taken from the Energy Department. Additionally, a questionnaire was distributed to acquire correlated independent variables with tumor markers records and 78 RWs participated in this study. Results indicated that after several years of tracing tumor markers, they all tend to increase in a normal range. Significantly, the Carcinoembryonic antigen (CEA) has increased by approximately 57% in RWs. Moreover, the smoking workers have a statistically significant change in CEA. Finally, the study has not shown any relationship between the radiation doses and tumor markers. In conclusion, to the best of the researchers’ knowledge, this is the first study to investigate the correlated tumor markers with low radiation doses among occupational worker. The researchers believe that these finding will contribute to ‘gap-filling’ in low dose effects, and demonstrate the importance of laboratory medical test in prediction of low doses effect. However, further investigations are needed to achieve results that are more accurate.